Nuclear medicine technologist education and training in Europe. Issue 6 (June 2015) - Matos, Ana C.; Massa, Raquel C.; Lucena, Filipa M.; Vaz, Tânia R.
<x xml:space="preserve">Abstract</x> Purpose The education and training of a nuclear medicine technologist (NMT) is not homogeneous among European countries, which leads to different scope of practices and, therefore, different technical skills are assigned. The goal of this research was to characterize the education and training of NMT in Europe. Materials and methods This study was based on a literature research to characterize the education and training of NMT and support the historical evolution of this profession. It was divided into two different phases: the first phase included analysis of scientific articles and the second phase included research of curricula that allow health professionals to work as NMT in Europe. Results The majority of the countries [N=31 (89%)] offer the NMT curriculum integrated into the high education system and only in four (11%) countries the education is provided by professional schools. The duration in each education system is not equal, varying in professional schools (2–3 years) and high education level system (2–4 years), which means that different European Credit Transfer and Accumulation System, such as 240, 230, 222, 210 or 180 European Credit Transfer and Accumulation System, are attributed to the graduates. The professional title and scope of the practice of NMT are different in different countries in Europe. In most countries of Europe, nuclear medicine training is not specific and curriculum does not demonstrate the Nuclear Medicine competencies performed in clinical practice. Conclusion The heterogeneity in education and training for NMT is an issue prevalent among European countries. For NMT professional development, there is a huge need to formalize and unify educational and training programmes in Europe. Video Abstract: http://links.lww.com/NMC/A39